Masjid Pedesaan sebagai Agen SDGs: Mengembangkan Kerangka Good Mosque Governance: Rural Mosques as SDGs Agents: Developing a Good Mosque Governance Framework - Ekaviana, Dessy; Mukhibad, Hasan; Ratnani, Mariana Ratih (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to formulate a contextual and practical concept of Good Mosque Governance (GMG) to improve mosque management quality and support the achievement of Sustainable Development Goals (SDGs), particularly in institutional governance, economic empowerment, and community participation. Design/Methodology/Approach: The study employs a qualitative approach using action research at An Najah Mosque, Giling Village, Semarang Regency. Data were collected through in-depth interviews, participatory observation, document analysis, and Focus Group Discussions (FGD). Data analysis was conducted thematically following five action research stages: diagnosing, action planning, action taking, evaluating, and learning. Findings: The results indicate that the implementation of GMG has the potential to support the achievement of SDG 1 (poverty alleviation), SDG 3 (public health), SDG 4 (quality education), SDG 8 (economic empowerment), SDG 10 (reduced inequalities), and SDG 16 (institutional strengthening). Research Implications: This concept is expected to serve as a practical reference for mosque managers and a theoretical contribution to the development of sustainable mosque governance.